Gadget Addiction Prevention Workshop in Children at An-Nuriyah Islamic Elementary School - Nurrohmatul Amaliyah; Supriansyah Supriansyah; Mia Dwi Anggraini; Siti Marifah (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
One of the things experienced by schools in the South Jakarta area is the problems that arise because students mostly hold gadgets when learning online. Based on the justification of the problem, the community service proposer team and partners held discussions and decided on the focus of the service to provide gadget addiction prevention training for children using the family link application. The method used in this Community Service activity is a method of training and mentoring. in this Community Service activity are, 1. There is an understanding between the An-Nuriyah Islamic Elementary School South Jakarta teacher and the school committee about the need for a family link application to monitor internet use in children 2. Can practice this PKM activity in the form of using a family link application for monitoring usage gadgets in children. The conclusions obtained from the Community Partnership Program activities held with the partners of SD Islam An-Nuriyah, South Jakarta, namely: 1. Understanding Psychological Knowledge of Elementary School Age Children 2. Understanding the Need for Supervision of Children Using Gadgets in Children 3. Pr how to use Google Family Link App.